Mr. Yowder and the train robbers - Rounds, Glen, 1906-2002. (New York : Holiday House, 1981)
Relates how Mr. Yowder outwits a gang of bank robbers with the help of some friendly rattlesnakes.
Keywords: Snakes -- Fiction; Robbers and outlaws -- Fiction; Humorous stories; West (U.S.) -- Fiction